The Potential of Aegle marmelos as a Co-Chemotherapeutic Antimetastatic Agent for Ovarian Cancer : a Review - wahyuni, Sri; Sutrisna, E.M.; Maryati, Maryati (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Aegle marmelos, commonly known as bael, has long been utilized in traditional medicine due to its diverse pharmacological activities, including antioxidant, antimicrobial, and anticancer properties. Recent studies have highlighted its potential as an anticancer agent through mechanisms such as apoptosis induction, proliferation inhibition, and suppression of metastasis. Ovarian cancer remains a significant cause of morbidity and mortality, primarily due to late-stage diagnosis, chemoresistance, and rapid metastatic progression. Co-chemotherapeutic agents derived from natural products, such as A. marmelos, may enhance standard chemotherapy efficacy, reduce resistance, and mitigate adverse effects. This review explores the potential of A. marmelos as a co-chemotherapeutic agent against metastatic ovarian cancer. The discussion covers its phytochemical composition, molecular mechanisms, cytotoxic activity across various cancer types, and its synergistic role in modulating resistance and tumor microenvironment. The therapeutic promise of A. marmelos in integrative cancer treatment strategies is emphasized as a research direction for future translational and clinical applications.